Effects of mood on how future events are generated and perceived - Hepburn, SR; Barnhofer, T; Williams, J (2006)
This study examined the effects of mood on cognitive processes underlying future thinking. Two groups of non-depressed volunteers generated future events before and after a positive or negative mood induction. The valence of each event was rated in the laboratory under induced mood, and then re-rated later at follow-up in recovered mood. Fluency for generating future events was affected by both mood inductions, with each group showing reduced fluency for mood-incongruent events under induced mood compared to baseline. There was no corresponding increase in fluency for mood-congruent events. Positive events were rated as more negative in sad mood than in recovered mood, but this did not mediate the effect of mood on generation of positive future events. The results are discussed with reference to hopelessness and reduced fluency for positive future events in deliberate self-harm patients. © 2006 Elsevier Ltd. All rights reserved.